Liver X Receptor Agonist Therapy Prevents Diffuse Alveolar Hemorrhage in Murine Lupus by Repolarizing Macrophages - Han, Shuhong; Zhuang, Haoyang; Shumyak, Stepan; Wu, Jingfan; Xie, Chao; Li, Hui; Yang, Li-Jun; Reeves, Westley H. (Frontiers in Immunology, 2018)
The generation of CD138+ phagocytic macrophages with an alternative (M2) phenotype that clear apoptotic cells from tissues is defective in lupus. Liver X receptor-α (LXRα) is an oxysterol-regulated transcription factor that promotes reverse cholesterol transport and alternative (M2) macrophage activation. Conversely, hypoxia-inducible factor 1-α (HIF1α) promotes classical (M1) macrophage activation. The objective of this study was to see if lupus can be treated by enhancing the generation of M2-like macrophages using LXR agonists. Peritoneal macrophages from pristane-treated mice had an M1 phenotype, high HIFα regulated phosphofructokinase and TNFα expression (quantitative PCR, flow cytometry), and low expression of the LXR α regulated gene ATP binding cassette subfamily A member 1 (Abca1) and Il10 vs. mice treated with mineral oil, a control inflammatory oil that does not cause lupus. Glycolytic metabolism (extracellular flux assays) and HIF1a expression were higher in pristane-treated mice (M1-like) whereas oxidative metabolism and LXRα expression were higher in mineral oil-treated mice (M2-like). Similarly, lupus patients’ monocytes exhibited low LXRα/ABCA1 and high HIF1α vs. controls. The LXR agonist T0901317 inhibited type I interferon and increased ABCA1 in lupus patients’ monocytes and in murine peritoneal macrophages. In vivo, T0901317 induced M2-like macrophage polarization and protected mice from diffuse alveolar hemorrhage, an often fatal complication of lupus. We conclude that end-organ damage (diffuse alveolar hemorrhage) in murine lupus can be prevented using an LXR agonist to correct a macrophage differentiation abnormality characteristic of lupus. LXR agonists also decrease inflammatory cytokine production by human lupus monocytes, suggesting that these agents may be have a role in the pharmacotherapy of lupus